Experimental Study on the Mechanical Properties of a New Type of Prefabricated Steel–Concrete-Composite Energy-Dissipation Shear-Wall System - Liuhuo Wang; Xiaohui Wu; Jie Feng; Yanfeng Wang; Dayang Wang (Buildings)
In order to enhance the energy-dissipation capacity and comprehensive seismic mechanical behavior of prefabricated steel–concrete-composite shear-wall structures, a new prefabricated composite energy-dissipation shear-wall system is proposed, which is composed of a shear-wall module and an energy-dissipation module connected by high-strength bolts. Four sets of comparative mechanical performance testing were conducted on the proposed composite energy-dissipation shear wall, including one set of traditional prefabricated composite shear-wall specimens (specimen TPCW) and three sets of composite energy-dissipation shear-wall specimens designed with different energy-dissipation modules (specimens PCEDW-A, PCEDW-B, and PCEDW-C). The results indicate that the proposed specimens PCEDW-A and PCEDW-B have a good bearing capacity and energy-dissipation characteristics, in which the number and range of concrete crack developments are lower than those of the traditional TPCW specimen under the same loading drift ratio condition. Compared with specimen TPCW, the ultimate bearing capacities of specimens PCEDW-A and PCEDW-B are increased by 13.76% and 17.15%, respectively. However, the equivalent damping ratio of specimen PCEDW-A is much higher than that of specimen PCEDW-B, and the former is nearly four times higher than the latter at the drift ratio of 1/100. Taking into account the load-bearing capacity and energy-dissipation characteristics, using a horizontal diamond-shaped perforated metal damper, specimen PCEDW-A exhibits the optimal mechanical behavior.